Preschool and primary school teachers’ attitudes toward students with type 1 diabetes: A cross-sectional study - María Yehisiri Martín–Báez; Candelaria de la Merced Díaz-González (PLoS ONE, 2026)
Introduction Type 1 diabetes mellitus (T1DM) is the most common chronic endocrine disorder in childhood, making teachers key agents in ensuring a safe school environment. The main objective of this study was to evaluate the attitudes and prejudices of teachers at Public Early Childhood and Primary Education Centres (ECPECs) in the municipality of San Bartolomé de Tirajana (SBTGC), on the island of Gran Canaria (Canary Islands, Spain), regarding the care of students with T1DM. Materials and methods A descriptive cross-sectional study was conducted. The target population consisted of 264 teachers from seven ECPECs schools in the municipality of SBTGC, Gran Canaria. Data collection was carried out using the validated instrument Teacher Negative Attitudes Index toward the Care of Students with Type 1 Diabetes Mellitus (INAPAD-18) , which allowed for the evaluation of teachers’ attitudes and provided an answer to the study’s main objective. The research was approved by the Research and Drug Ethics Committee (CEIm) of Las Palmas. Results The final sample consisted of 126 participants, representing a participation rate of 47.72%, which did not reach the size required for statistical representativeness. A total of 15.87% of teachers reported currently having students diagnosed with T1DM. The mean number of years of experience working with students with this condition was 3.77 years [0–35years]. A marked gender disparity was observed, with a predominance of women (84.12%). The mean score obtained on the INAPAD-18 questionnaire was 47.02 (range: 18–90). In this instrument, lower scores indicate more favourable attitudes toward the care of students with T1DM. Although male participants showed more favourable attitudes compared to their women, this difference was not statistically significant (p > 0.05). Discussion/Conclusion The results indicate generally favourable attitudes, with moderately low INAPAD-18 scores. However, slight deficiencies were observed in teachers’ training and perception, consistent with findings from previous similar studies. The ECPEC schools Juan Grande and Las Dunas stood out for demonstrating the most positive attitudes. It is necessary for educational institutions to implement specific measures aimed at teacher training in order to improve attitudes and ensure appropriate attention to the needs of students with T1DM.